2000
DOI: 10.1074/jbc.m910406199
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytidine to Uridine Editing on Cytoplasmic Apolipoprotein B mRNA by Overexpressing APOBEC-1

Abstract: Post-transcriptional editing of apolipoprotein B (apoB) mRNA is regulated in hepatic cells to achieve a steady state proportion of edited and unedited RNA molecules. This activity is catalyzed by APOBEC-1 (apoB mRNA editing catalytic subunit 1) in what has been widely accepted as nuclear event occurring during or after mRNA splicing. Introns impair the efficiency of editing within an adjacent exon in a distance-dependent manner in reporter RNAs. We show here that this inhibition can be overcome by overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 39 publications
2
58
2
Order By: Relevance
“…Nor does it occur when rat hepatic editing efficiencies are stimulated by metabolic or hormonal manipulations [49,50]. Promiscuous editing appears to be unique to cells in which APOBEC-1 has been artificially overexpressed [10,40,47] and is observed under these conditions on both nuclear and cytoplasmic transcripts [9]. The results presented in Figures 3 and 4 are therefore the first demonstration of promiscuous editing in the nucleus without the exogenous overexpression of APOBEC-1.…”
Section: Blocking the Commitment Of Transcripts To The Splicing Pathwmentioning
confidence: 54%
See 3 more Smart Citations
“…Nor does it occur when rat hepatic editing efficiencies are stimulated by metabolic or hormonal manipulations [49,50]. Promiscuous editing appears to be unique to cells in which APOBEC-1 has been artificially overexpressed [10,40,47] and is observed under these conditions on both nuclear and cytoplasmic transcripts [9]. The results presented in Figures 3 and 4 are therefore the first demonstration of promiscuous editing in the nucleus without the exogenous overexpression of APOBEC-1.…”
Section: Blocking the Commitment Of Transcripts To The Splicing Pathwmentioning
confidence: 54%
“…However, the editing efficiency was enhanced 5-fold when the Rev protein was coexpressed. Given that editing in the cytoplasm has never been demonstrated in wild-type McArdle cells [9], nor would it be driven by an increase in apoB RNA abundance in the cytoplasm [10], we propose that the enhanced editing occurred in the nucleus as a consequence of pre-mRNAs by-passing commitment to the spliceosome assembly and\or RNA export pathways. We cannot formally exclude the alternative explanation that unspliced CAT-apoB chimaeric RNAs were edited in the cytoplasm.…”
Section: Blocking the Commitment Of Transcripts To The Splicing Pathwmentioning
confidence: 99%
See 2 more Smart Citations
“…17,30,61 Nonetheless, it has been shown that overexpression of APOBEC1 can induce editing also in the cytoplasm. 62 Considering that both APOBEC1 and ACF appear localized in different compartments depending on the cells in which they are expressed, 30,59,62-64 we wanted to assess the weight of the nuclear and of the cytoplasmic component of RNA editing in our model system.…”
Section: Rna Editing In Nucleus and Cytoplasmmentioning
confidence: 99%